Primary penile lymphoma: the use of PET-CT for accurate staging and response monitoring - Sellam Karunanithi; Punit Sharma; Niraj Naswa; Ramya Soundararajan; Tushar Mohapatra; Arun Malhotra; Chandrasekhar Bal; Rakesh Kumar (Diagnostic and Interventional Radiology, 2013)

(untitled)
Primary penile lymphoma is an extremely rare neoplasm. We present a case of 63-year-old man with painless diffuse pe- nile swelling and retention of urine. Biopsy from the penile swelling demonstrated CD20+ diffuse large B-cell lymphoma. Staging was performed using ﬂuorine-18-ﬂuorodeoxyglucose (FDG) positron emission tomography-computed tomography (PET-CT) and revealed a FDG avid penile mass with enlarged and FDG avid multiple inguinal and aortocaval lymph nodes. A follow-up FDG PET-CT scan after eight cycles of combina- tion chemotherapy showed complete remission of the dis- ease. Thus, FDG PET-CT should be integrated in management protocols of rare primary penile lymphoma.